2022
DOI: 10.3390/ijerph19105870
|View full text |Cite
|
Sign up to set email alerts
|

A Network Comparison of Motives behind Online Sexual Activities and Problematic Pornography Use during the COVID-19 Outbreak and the Post-Pandemic Period

Abstract: Many researchers have considered whether online sexual activities (OSAs) increased over the course of the COVID-19 pandemic and whether these have led to an increase in problematic pornography use (PPU). This study investigated the impact of COVID-19 on PPU through pornography use motivations (PUMs) and OSAs to develop a better understanding of the mechanism and changes affecting PPU. Two groups of Chinese adults were recruited during the initial months of the pandemic (April 2020, n1 = 496) and the post-pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…This mismatch between the level of analysis and the theoretical underpinnings of network theory (which emphasises individual-level symptom interactions) is a recognised limitation of the network approach (Neal et al, 2017). Alternative person-centred approaches (e.g., latent profile analysis) may therefore shed light on relationships among variables that differ across individuals in ways that network analysis is not equipped to do ( Chen et al, 2022 ; Jiang et al, 2022 ). Additional (missing) nodes also represent a key limitation of network analysis (Neal & Neal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This mismatch between the level of analysis and the theoretical underpinnings of network theory (which emphasises individual-level symptom interactions) is a recognised limitation of the network approach (Neal et al, 2017). Alternative person-centred approaches (e.g., latent profile analysis) may therefore shed light on relationships among variables that differ across individuals in ways that network analysis is not equipped to do ( Chen et al, 2022 ; Jiang et al, 2022 ). Additional (missing) nodes also represent a key limitation of network analysis (Neal & Neal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from research that identified unique motives for the problematic use of specific types of online content also suggests there are likely core motives (e.g., motives to cope with negative emotions) that influence the problematic engagement in content generally, irrespective of the type (A. Chen & Roberts, 2019;Jiang et al, 2022;Melodia et al, 2022). A body of literature has focussed on identifying what core motives influence generalised PSU (e.g., C. Chen et al, 2017;Wang et al, 2015;, but there remains a lack of consensus on what these motives are.…”
Section: Motives For Generalised and Specific Problematic Smartphone Usementioning
confidence: 99%
“…Kehadiran internet sangat membantu kehidupan manusia dan juga menyeretnya dalam kemaksiatan pornografi (Keshav et al, 2022;Hidayat et al, 2022). Pornografi menurut Undang-Undang Nomor 44 Tahun 2008 merupakan gambar, sketsa, ilustrasi, foto, tulisan, suara, bunyi, gambar bergerak, animasi, kartun, percakapan, gerak tubuh, atau bentuk pesan lainnya melalui berbagai bentuk media komunikasi dan/atau pertunjukan di muka umum, yang memuat kecabulan atau eksploitasi seksual yang melanggar norma kesusilaan dalam masyarakat (Sánchez-Lamadrid et al, 2022;Jiang et al, 2022).…”
Section: Pendahuluanunclassified